The News Media at war : the clash of Western and Arab networks in the Middle East - Cherkaoui, Tarek (London : I.B. Tauris & Co. Ltd, 2017)
"During the 2003 Iraq War, American news media found it difficult to convey their pro-war perspective outside the United States. Since the war was unpopular in many parts of the world, failure to win hearts and minds -- particularly in the Middle East -- represented a significant setback for American soft power. This book studies the complexities of media coverage of the Iraq War against a backdrop of clashing Orientalist and pan-Arab paradigms, through the examples of two leading global and transnational news networks, CNN International (CNNI) and Al Jazeera." -- Publisher's description
War, Propaganda, and the Mobilisation of Frames -- Orientalism, Terrorism, and American Media Discourse -- CNNI Framings of Middle East Conflict, 1991-2001 -- The Origins of Modern Arab Nationalism -- The Prospect of War in Iraq: Frames, Propaganda, and Debate -- Hostilities Begin: 'Decapitation Strike', 'Shock and Awe', and Contesting Realities -- Journalists as Combatants: US Bombing of Al Jazeera's Office and the Palestine Hotel -- Liberation vs. Occupation: The Toppling of Saddam's Statue.
Includes bibliographical references (pages 265-301) and index.
Text in English.
Keywords: Iraq War, 2003-2011 -- Press coverage -- United States; Iraq War, 2003-2011 -- Press coverage -- Arab countries